Olivine‐Type MgMn0.5Zn0.5SiO4 Cathode for Mg‐Batteries: Experimental Studies and First Principles Calculations. Issue 12 (12th January 2023) - Pérez‐Vicente, Carlos; Rubio, Saúl; Ruiz, Rafaela; Zuo, Wenhua; Liang, Ziteng; Yang, Yong; Ortiz, Gregorio F.
Abstract: Magnesium driven reaction in olivine‐type MgMn0.5 Zn0.5 SiO4 structure is subject of study by experimental tests and density functional theory (DFT) calculations. The partial replacement of Mn in Oh sites by other divalent metal such as Zn to get MgMn0.5 Zn0.5 SiO4 cathode is successfully developed by a simple sol–gel method. Its comparison with the well‐known MgMnSiO4 olivine‐type structure with (Mg)M1 (Mn)M2 SiO4 cations distribution serves as the basis of this study to understand the structure, and the magnesium extraction/insertion properties of novel olivine‐type (Mg)M1 (Mn0.5 Zn0.5 )M2 SiO4 composition. This work foresees to extend the study to others divalent elements in olivine‐type (Mg)M1 (Mn0.5 M0.5 )M2 SiO4 structure with M = Fe, Ca, Mg, and Ni by DFT calculations. The obtained results indicate that the energy density can be attuned between 520 and 440 W h kg −1 based on two properties of atomic weight and redox chemistry. The presented results commit to open new paths toward development of cathodes materials for Mg batteries. Abstract : A first scientific approach dealing with MgMn0.5 M0.5 SiO4 (M = Zn, Ca, Mg, Fe, Ni) whose DFT calculations predict different redox chemistries. Rietveld refinement confirms that the replacement of Mn 2+ in OH sites by a divalent metal can be successfully developed. The assembled Mg/MgMn0.5 Zn0.5 SiO4 cell exhibits 120 mAhg −1 capacity and 2V average cell potential.